2009
DOI: 10.1007/s00125-009-1340-9
|View full text |Cite
|
Sign up to set email alerts
|

Early autonomic dysfunction in type 1 diabetes: a reversible disorder?

Abstract: Aims/hypothesis Cardiac autonomic neuropathy is associated with increased morbidity and mortality rates in patients with type 1 diabetes. The prevalence of early autonomic abnormalities is relatively high compared with the frequency of manifest clinical abnormalities. Thus, early autonomic dysfunction could to some extent be functional and might lead to an organic disease in a subgroup of patients only. If this is true, manoeuvres such as slow deep-breathing, which can improve baroreflex sensitivity (BRS) in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 51 publications
8
77
0
2
Order By: Relevance
“…As none of the methods has been proved to be superior to the others, we used a set of four different tests and present the BRS data as the average of these methods. This proved to be a more robust estimate than the use of single tests [7,23].…”
Section: Study Populationmentioning
confidence: 94%
See 3 more Smart Citations
“…As none of the methods has been proved to be superior to the others, we used a set of four different tests and present the BRS data as the average of these methods. This proved to be a more robust estimate than the use of single tests [7,23].…”
Section: Study Populationmentioning
confidence: 94%
“…Diabetic neuropathy has conventionally been considered to be an irreversible, organic process [6]. However, in a previous study we demonstrated that, in patients with type 1 diabetes and early autonomic impairment as indicated by reduced baroreflex sensitivity (BRS), the BRS was in fact normalised during slow breathing [7]. The importance of this finding lies in the fact that reduced BRS is an established marker of poor prognosis in cardiovascular medicine [8][9][10], and also an early marker of autonomic alteration in diabetes [11][12][13].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Much like in diabetic Akita mice, functional and potentially reversible reductions in parasympathetic heart rate control can occur in human beings. More detailed physiologic (14) or pharmacologic (15) tests may be required to differentiate functional and structural parasympathetic dysfunction in diabetic patients. Furthermore, the cause of the change in parasympathetic heart rate control is difficult to localize.…”
mentioning
confidence: 99%